Effects of Quercetin supplementation on endurance performance and maximal oxygen consumption: A meta-analysis - Pelletier, D. M.; Lacerte, G.; Goulet, E. D. B. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Lately, the effect of quercetin supplementation (QS) on endurance performance (EP) and maximal oxygen consumption (VO2max) has been receiving much scientific and media attention. Therefore, a meta-analysis was performed to determine QS`s ergogenic value on these variables. Studies were located with database searches (PubMed and SPORTDiscus) and cross-referencing. Outcomes represent mean percentage changes in EP (measured via power output) and VO2max between QS and placebo. Random-effects model meta-regression, mixed-effects model analog to the ANOVA, random-effects weighted mean effect summary, and magnitudebased inferences analyses were used to delineate the effects of QS. Seven research articles (representing 288 subjects) were included, producing 4 VO2max and 10 EP effect estimates. Mean QS daily intake and duration were, respectively, 960 ± 127 mg and 26 ± 24 d for the EP outcome and 1,000 ± 0 mg and 8 ± 23 d for the VO2max outcome. EP was assessed during exercise with a mean duration of 79 ± 82 min. Overall, QS improved EP by 0.74% (95% CI: 0.10-1.39, p = .02) compared with placebo. However, only in untrained individuals (0.83% ± 0.78%, p = .02) did QS significantly improve EP (trained individuals: 0.09% ± 2.15%, p = .92). There was no relationship between QS duration and EP (p = .69). Overall, QS increased VO2max by 1.94% (95% CI: 0.30-3.59, p = .02). Magnitude-based inferences suggest that the effect of QS on EP and VO2max is likely to be trivial for both trained and untrained individuals. In conclusion, this meta-analysis indicates that QS is unlikely to prove ergogenic for aerobic-oriented exercises in trained and untrained individuals.